Assessment of Oxidative Stress Parameters for some of Baghdad City Fuel Stations Workers - Abdulameer, Abdulameer Hassan; Hussein, Saba Zuhair (Iraqi Journal of Science, 2023)
Because of inhalation of the volatile substances and unintended ingestion, the risk of health problems for fuelling employees exposed to gasoline vapours in gas stations is increased. Therefore, the goal of the study was to compare the oxidative stress state of healthy volunteers, who served as the control group, to Iraqi male fuelling staff, who served as the exposed groups. The levels of total oxidant status (TOS), total antioxidant status (TAS) and oxidative stress index (OSI), malondialdehyde (MDA), Uric acid (UA), and total peroxidase activity were measured. A total of 102 subjects divided into three groups according to the duration of fuel vapours exposure: 25 exposed for 1-10 years (G1), 50 exposed for 11-19 years (G2) and 27 exposed for ≥ 20 years (G3), as well as 50 healthy people as a control group (C). The results exhibited that the levels of TOS, OSI, MDA, and total peroxidase activity were highly significant increased in all exposed groups (G1, G2 & G3) as compared to the C. A highly significant decrease was observed in TAS levels in all exposed groups in comparison with the C, while there was no significant difference in UA levels in all studied groups. The exposure to petrol associated with significant increase of TOS, OSI, MDA and total peroxidase activity with a significant decrease of TAS among workers in fuel stations and they increased oxidative stress, which likely resulted in negative impacts on human health later on as a result of prolonged labour at gas stations.